2019
DOI: 10.1039/c9ta00709a
|View full text |Cite
|
Sign up to set email alerts
|

In situ N-doped carbon modified (Co0.5Ni0.5)9S8 solid-solution hollow spheres as high-capacity anodes for sodium-ion batteries

Abstract: The in situ N-doped carbon modified (Co0.5Ni0.5)9S8 solid-solution hollow spheres can be explored as high-capacity anodes for sodium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…As shown in Figure b, the value of b can be calculated from the slope of log( i ) versus log( ν ), and was 0.97 and 0.89 for the oxidation and reduction processes, respectively. This indicated that both the diffusion‐controlled process and pseudocapacitive behavior contributed to the Li + insertion/extraction process . Each fraction of contribution to the current at a specific potential can be estimated quantitatively by the equation i (V)=k 1 ν +k 2 ν 1/2 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure b, the value of b can be calculated from the slope of log( i ) versus log( ν ), and was 0.97 and 0.89 for the oxidation and reduction processes, respectively. This indicated that both the diffusion‐controlled process and pseudocapacitive behavior contributed to the Li + insertion/extraction process . Each fraction of contribution to the current at a specific potential can be estimated quantitatively by the equation i (V)=k 1 ν +k 2 ν 1/2 .…”
Section: Resultsmentioning
confidence: 99%
“…The capacitive process including physical adsorption/desorption of electrolyte ions and fast surface redox reactions (capacitive contributions), and the diffusion process is kinetic sluggish redox reactions controlled by the diffusion of electrolyte ion (diffusion-controlled contributions). This method is suitable for batteries due to the narrow range of sweep rates and is widely used in many articles [47][48][49]. For supercapacitors, however, on account of the large range of sweep rate, this method is not appropriate.…”
Section: Electrochemical Analysismentioning
confidence: 99%
“…Over recent years, BMSs with various morphologies have been successfully synthesized via solvothermal method. For example, NiCo 2 S 4 nanodots with N-doped carbon (NiCo 2 S 4 @NC) (Li S. et al, 2019), NiCo 2 S 4 hollow prism wrapped in reduced graphene oxide (rGO) (Zhang et al, 2018), N/S-rGO@ZnSnS 3 amorphous ZnSnS 3 @rGO (Liu et al, 2019), ((Ni 0.3 Co 0.7 ) 9 S 8 /N-CNTs/rGO) (Lv et al, 2018), (Co 0.5 Ni 0.5 ) 9 S 8 /N-C) nanoparticles (Cao et al, 2019), CuCo 2 S 4 /rGO nanoparticles (Li Q. et al, 2019), and so forth. These nanostructured materials synthesized through solvothermal method possess strong controllability, excellent electrochemical performance, fast ions, and electron transfer paths and outstanding rate capability (Zhao and Manthiram, 2015;Liu et al, 2017;Jia et al, 2018;Chen et al, 2019).…”
Section: Synthesis Of Bms With Nanostructures Solvothermal Methodsmentioning
confidence: 99%
“…The impressive rate capability of 596.1 mAh g −1 was achieved at 10 A g −1 with a high capacity retention of 60.2% at 0.1 A g −1 , demonstrating an excellent rate performance. As a result of carbon modification and the hierarchical sphere structures, high electrical conductivity, and mechanical stability were achieved during the cycling process (Cao et al, 2019).…”
Section: Applications In Sibs Transition Bmssmentioning
confidence: 99%